Meta-analysis of residential exposure to radon gas and lung cancer - Pavia Maria; Bianco Aida; Pileggi Claudia; Angelillo Italo F. (The World Health Organization, 2003)
OBJECTIVES: To investigate the relation between residential exposure to radon and lung cancer. METHODS: A literature search was performed using Medline and other sources. The quality of studies was assessed. Adjusted odds ratios with 95% confidence intervals (CI) for the risk of lung cancer among categories of levels of exposure to radon were extracted. For each study, a weighted log-linear regression analysis of the adjusted odds ratios was performed according to radon concentration. The random effect model was used to combine values from single studies. Separate meta-analyses were performed on results from studies grouped with similar characteristics or with quality scores above or equal to the median. FINDINGS: Seventeen case-control studies were included in the meta-analysis. Quality scoring for individual studies ranged from 0.45 to 0.77 (median, 0.64). Meta-analysis based on exposure at 150 Bq/m³ gave a pooled odds ratio estimate of 1.24 (95% CI, 1.11-1.38), which indicated a potential effect of residential exposure to radon on the risk of lung cancer. Pooled estimates of fitted odds ratios at several levels of radon exposure were all significantly different from unity - ranging from 1.07 at 50 Bq/m³ to 1.43 at 250 Bq/m³. No remarkable differences from the baseline analysis were found for odds ratios from sensitivity analyses of studies in which >75% of eligible cases were recruited (1.12, 1.00-1.25) and studies that included only women (1.29, 1.04-1.60). CONCLUSION: Although no definitive conclusions may be drawn, our results suggest a dose-response relation between residential exposure to radon and the risk of lung cancer. They support the need to develop strategies to reduce human exposure to radon.